Obecność osoby nauczającej w zadaniach zorientowanych na samodzielną pracę uczniów w środowisku wirtualnym - Górecka, Joanna (Neofilolog, 2019)
The present paper is a report on the author’s own teaching experiences and focuses on the creation of learning situations in a virtual environment. The main aim is to define the characteristics of a learning situation in such an environment. More precisely, the paper focuses on: (1) answering the ques-tion whether – and to what extent – current studies on the model of hybrid education provide the necessary information useful in developing the pro-fessional competence of teachers willing to use ICT tools in their work, and, (2) drawing conclusions about the author’s own teaching experiences, whose aim is to determine what types of actions on the part of the teacher, concerning on the one hand, the task’s scenario and, on the other hand, his or her intervention in a virtual environment, can contribute to learning. The article emphasizes the necessity of perceiving interaction in a virtual envi-ronment as a separate communicative situation which requires specific skills both on the part of the teacher and the learner.